Short-Run Efficiency and the Organization of the Electric Power Industry - Hughes, William R. (Quarterly Journal of Economics, 1962)
I. Introduction, 592. — II. Organization of the U. S. electric power industry, 593. — III. The yardstick, 595. — IV. Short-run optimization problems of electric utilities, 597. — V. Interfirm coordination in New England, 599. — VI. Conclusions, 612.